Green Concrete: Pemanfaatan Sampah Non Organik Tutup Botol “Kempyeng” Dan Serbuk Kaca Sebagai Material Susbtitusi Parsial Beton - Pranadiarso, Tedy; Junaidi, Imam; Ngibadah, Irsyadul (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2025)
The construction industry in Indonesia continues to grow. Additionally, data from the Ministry of Environment shows that the amount of non-organic waste accumulated over the four years from 2020 to 2023 has also increased. The innovation in this study is the use of non-organic waste from ‘Kempyeng’ bottle caps and glass as a solution for environmentally friendly concrete (Green Concrete). This study aims to identification the optimal composition and analize percentage influence on compressive strength and bulk density from the use of non-organic waste bottle caps ‘Kempyeng’ and glass powder as partial substitutes for cement and gravel. The study used bottle cap ‘Kempyeng’ compositions of 0%, 2%, 4%, 5%, and 7%. Meanwhile, the glass powder mixture composition was 0%, 5%, and 8%. Laboratory test results showed the optimal composition for partial substitution of cement and gravel was 5% glass and 4% kempyeng, with concrete compressive strength at 28 days of 26.92 MPa and bulk density of 2360.7 kg/m³. This proportion also increased the compressive strength by 6.65% and reduced the bulk density by 0.82% compared to normal concrete. With these results, glass powder and ‘Kempyeng’ bottle caps can be used as partial substitutes for cement and gravel in concrete mixtures.